Leading topics and ideas of new Korean poetry of the XX century - Saydazimova, Umida Turakhanovna (Linguistics and Culture Review, 2021)
This article discusses the leading themes and ideas of new Korean poetry of the twentieth century. Many Korean youths went to Japan to study. Here they studied in the faculties of literature and were able to get acquainted with Western European, English, and Russian literature. Western literature had a significant influence on the formation of modern Korean literature.